2019
DOI: 10.1155/2019/3210710
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Microsatellite Instability Pathway in Outcome of Colon Cancer in Moroccan Population

Abstract: Background Tumors with microsatellite instability (MSI tumors) have distinct clinicopathological features. However, the relation between these tumor subtypes and survival in colon cancer remains controversial. The aim of this study was to evaluate the overall survival (OS) in patients with MSI phenotype, in FES population. Methods The expression of MMR proteins was evaluated by immunohistochemistry for 330 patients. BRAF, KRAS, and NRAS mutations were examined by Sanger sequencing and pyrosequencing methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…We observed that high tumor budding was more common in MSS tumors, which is consistent with ndings reported by previous studies (7,19,20). It was showed that MSS tumors were signi cantly correlated with shorter overall survival of CC patients (21).…”
Section: Discussionsupporting
confidence: 93%
“…We observed that high tumor budding was more common in MSS tumors, which is consistent with ndings reported by previous studies (7,19,20). It was showed that MSS tumors were signi cantly correlated with shorter overall survival of CC patients (21).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the molecular epidemiological study conducted by Gonsalves et al [ 36 ] has shown that KRAS codon 13 mutations were associated with deficient mismatch repair phenotype and poor differentiation. These parameters were reported to be predictors of worse OS [ 37 ]. These results may explain the worse survival observed in patients with codon 13 mutations CC, as reported by Modest et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MSI is now considered an indicator of tumor types in patients with COAD. In addition, COAD patients with high MSI showed better checkpoint inhibitor response and survival in both early and late clinical stages ( El Agy et al, 2019 ; Allan et al, 2020 ; Dzunic et al, 2020 ). In our study, both the TMB and MSI of COAD were positively correlated with the expression of MALT1, which supports our claim that MALT1 may be a good indicator of potential drug response (and MSI), as well as in COAD.…”
Section: Discussionmentioning
confidence: 99%